Los escenarios educativos en la actualidad: historicidad, reflexiones y propuestas para la mejora educativa en el Ecuador. - Figueroa Martínez, Ericka Jazmin (2017)
The scenarios in the educational process are fundamental in the development of the Ecuadorian evolution, the projection in time of this academic cause through a bibliographic design, the reflections that are proposed, is of a political nature since they are developed according to the spirit of governments with external influence. The scenarios have been created for the purposes of the members of the community, imaginary, minorities.The objective of this work is to reflect on realities and challenges imposed by educational scenarios, as well as to generate proposals for the improvement of educational processes in the Ecuadorian sphere, from an approach of respect for human diversity and educational inclusion.